Effect of Typhoon Kalmaegi (2014) on northern South China Sea explored using Muti-platform satellite and buoy observations data. (January 2020) - Wu, Renhao; Zhang, Han; Chen, Dake
Highlights: The current velocity to the right side of the track decays faster than that to the left side. Water temperature response to the right side of the track exhibits a three-layered 'cooling–warming–cooling' structure in the vertical. Storms with tracks similar to that of Kalmaegi (2014) may induce similar maximum cooling in the northern SCS. Abstract: Based on observational data from a buoy/mooring array and satellite remote sensing data for sea-surface winds, temperature, and height during the passage of Typhoon Kalmaegi (2014), a systematic analysis is performed on the atmospheric and oceanic variables of winds, sea-level air pressure, surface air temperature, sensible and latent heat fluxes, rainfall, water temperature, salinity, and ocean currents. Kalmaegi passed through the South China Sea (SCS) with a mean non-dimensional speed of ~2.87, typical of a fast-moving storm with a predominantly baroclinic oceanic response. In addition to some well-documented response features such as rightward-biased intensifications in sea-surface cooling and currents, a much deeper mixed layer to the right side of the storm, and a strong near-inertial oscillation in the thermocline, we here identify several new features, as follows. (1) The current velocity to the right side of the track decays faster than that to the left side. (2) On the right side of the track, the typhoon-induced water temperature anomaly exhibits a three-layered 'cooling–warming–cooling' structure in the vertical, with salinity and density anomaly profiles sharing a similar pattern. (3) On the left side of the track, the whole upper ocean is cooled, whereas salinity shows no variation in the uppermost 20-m layer, with a negative anomaly for water at depths from 20 to 50 m and a positive anomaly below 50 m. The associated mechanisms are discussed in the text. (4) The storm-induced maximum cooling is not unique to Kalmaegi (2014). In fact, storms with tracks similar to that of Kalmaegi (2014) may induce similar maximum cooling in the northern SCS, which may be useful in predictions of where such storms would induce the maximum cooling.